2015
DOI: 10.1186/s13167-015-0046-y
|View full text |Cite
|
Sign up to set email alerts
|

HTRF: a technology tailored for biomarker determination—novel analytical detection system suitable for detection of specific autoimmune antibodies as biomarkers in nanogram level in different body fluids

Abstract: BackgroundClassical methods of gene product analysis such as binding assays (e.g., ELISA, protein chip technology) are generally time-consuming, lab-intensive, less sensitive, and lack high-throughput capacity. In addition, all existing methods used to measure proteins necessitate multiple divisions of the original sample and individual tests carried out for each substance, with an associated cost for each test.MethodTogether with a small biotech company, we developed a new and innovative analytical detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The focus is predominantly on socially significant diseases with dental caries-related diseases being one of the most important ones due to their huge impact on people's social lives [2]. The analysis of modern publication on the development of cutting-edge medical technologies [3,4], i.e. on the approaches to early caries prevention [5][6][7], suggests that the topic is a national top priority.…”
Section: Introductionmentioning
confidence: 99%
“…The focus is predominantly on socially significant diseases with dental caries-related diseases being one of the most important ones due to their huge impact on people's social lives [2]. The analysis of modern publication on the development of cutting-edge medical technologies [3,4], i.e. on the approaches to early caries prevention [5][6][7], suggests that the topic is a national top priority.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the formation of a double-antibody sandwich structure requires a suitable ratio of antigen to the antibody. Meanwhile, it is found that the antigen concentration is not as high as possible, and it may lead to the occurrence of HOOK effect and produce false-negative results caused by inappropriate proportion of antigen and antibody [47]. Through ELISA and standard antigen, the optimum ratio of antigen and antibody is screened out.…”
Section: Discussionmentioning
confidence: 99%
“…it is more convenient for minimal sample volume; it is able to measure 384 samples simultaneously, and; process time is quicker than ELISA (Einhorn and Krapfenbauer, 2015).…”
Section: Discussionmentioning
confidence: 99%